Banking Licences, Bailouts and Regulator Ability - Morrison, A (2004)
I analyse a model in which it is socially optimal for banks to manage depositor funds but in which concerns about fraud discourage depositing and justify regulation. The regulator screens bankers and decides the level of charter value which they will receive as incentive to prevent fraud. She can also encourage deposits by insuring them. The optimal policy depends upon the regulator's screening ability: high ability regulators rely upon charter value and low ability regulators rely upon deposit insurance. I relate these findings to the regulation of transition economy banks, to operational risk management, and to banking competition policy.